La damnation de Faust légende dramatique en quatre parties - Berlioz, Hector 1803-1869 (Erato, 2019)
"The most dramatic piece that Berlioz ever wrote," is how conductor John Nelson describes La Damnation de Faust. The composer designated this thrilling hybrid of oratorio and opera a 'légende dramatique'. Following in the triumphant footsteps of Les Troyens, also recorded at the Auditorium Erasme in Strasbourg, this performance reunites Nelson and the Orchestre Philharmonique de Strasbourg with singers Michael Spyres, Joyce DiDonato and Nicolas Courjal."--prestomusic.com
Interpreten unter anderem: Joyce DiDonato (Marguerite). Michael Spyres (Faust). Nicolas Courjal (Méphistophélès). Alexandre Duhamel (Brander). Coro Gulbenkian. Les Petits Chanteurs de Strasbourg - Maîtrise de l'opéra national du Rhin. Strasbourg Philharmonic Orchestra. John Nelson (Dirigent)
Live-Aufnahme: Straßburg, Salle Érasme, April 2019
Includes a 41-minute bonus DVD with video highlights of the concert performance on 25 april 2019
Keywords: Operas; Live sound recordings; CD